Rapid discrimination of the native medicinal plant Adenostemma lavenia from its adulterants using PCR-RFLP - Wu,Kunchang; Liu,Yunchen; Yang,Bocheng; Kung,Yenying; Chang,Kaiwei; Lee,Mengshiou (PeerJ, 2022)
Background In Taiwan, the aerial part of Adenostemma lavenia (Al) is used in the form of herbal tea or in a folk remedy primarily to mitigate inflammatory conditions in the lungs and liver. Due to the excellent health benefits of Al against inflammation, it has become increasingly crucial and in great demand during the COVID-19 pandemic. However, Al has been found to be adulterated with Wedelia biflora, Sigesbeckia orientalis, and/or Wedelia chinensis because of similarities in appearance and vernacular names. Methods This study aimed to develop a PCR-RFLP DNA molecular method for the authentication of Al. The restriction enzyme BsrI was used according to the sequencing and alignment results of PCR products in the ITS2 regions of Al and its adulterants. Gel electrophoresis resulted in the clear separation of Al and its adulterants into two distinct categories. Results In conclusion, the PCR-RFLP authentication method developed herein provides an easy, rapid, and accurate method to distinguish Al from its adulterants to assure user health and safety.
Keywords: Adenostemma lavenia; Identification of origin; Molecular identification; Functional food